Greek Medical Papyri Text, Context, Hypertext - Reggiani, Nicola (Archiv für Papyrusforschung und verwandte Gebiete - Beihefte, 2019)
This volume, authored by outstanding papyrologists and historians of ancient medicine, deals with topics focused on the papyrological evidence of ancient medical texts and contexts. The first part contains some new reflections on important sources such as the Anonymus Londinensis and the Hippocratic corpus, the second part collects papers about the "doctors' context", and the final part is focused on the digitisation of the medical papyri.